Market pricing of credit rating signals - Magdalena Grothe (European Central Bank (ECB), 2013)
This paper contributes new evidence on market pricing of rating changes. We examine the relation between spreads and ratings for a very large and comprehensive sample of corporate bonds, which allows us to test for country- and industry-specific effects, as well as to explore the differences between the calm and distressed market conditions. The results show that the effects of rating actions on market prices are significant and depend on the current state of the market. While during favourable market conditions rating actions are not crucial for market pricing, they become very significant in the periods of crisis.
Keywords: G12; G14; G01; G21; 330; corporate bond spreads; credit ratings; pricing of risk